Effectiveness of 14-15 years old tennis players’ competition functioning considering correction of their psychological fitness - Makuts, T.B. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to determination influence of individualized psychological training on effectiveness of 14-15 years old tennis players’ competition functioning. Material: in the research 24 tennis players of 14-15 years’ age participated. Individualized psychological training consisted of 15 sessions of total duration of 1.5 months. Results: We substantiated necessity of individualized approach to tennis players’ psychological training. Individual psychological profiles for tennis players, which determined content of psychological training and their selection, were worked out. Informative indicators for assessment of 14-15 years old tennis players’ competition functioning were determined: 1) percentage of won and lost scores at the account of own actions; 2) integral criteria of tennis players’ competition functioning assessment (coefficient of stability and effectiveness; complex indicator of efficiency). Conclusions: it is recommended to consider individual potentials and bents of sportsmen in the course of psychological training.